Evaluating the stress and its association with stressors among the dental undergraduate students of Kanpur city, India: A cross-sectional study - Rahul Srivastava; Bhuvan Jyoti; Devina Pradhan; Manoj Kumar; Pankaj Priyadarshi (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Dental education can be a critical wellspring of stress among dental students, and studies have observed higher levels of stress among dental students than in the all-inclusive community. The present study aims to evaluate the perceived stress among dental undergraduate students, the sources of stress, and an association of perceived stress with sociodemographic characteristics and various stressors. MATERIALS AND METHODS: A cross-sectional study was conducted among 380 undergraduate dental students (from 1st year to final year) in a private dental college, Kanpur. A self-administered questionnaire was used to collect data regarding sociodemographic profile, perceived stress using Perceived Stress Scale-14, and academic, psychosocial, and environmental stressors. Data were analyzed using IBM SPSS Statistics-Version 21 (IBM Corp. Released 2012. IBM SPSS Statistics for Windows, Version 21.0, Armonk, NY, USA: IBM Corp.). RESULTS: The mean perceived stress score was 30.25 ± 1.914. The median perceived stress score was 30. Statistically significant (P < 0.001) values were found for higher age group and year of studying Bachelor of Dental Surgery (BDS) were important sociodemographic determinant of stress. Vastness of academic curricula, frequency of examination (P < 0.05), and fear of failure/poor performance in examinations were important academic determinants of stress. High parental expectations and family problems were important psychosocial stressors. Accommodation away from home was an important predictor of stress (P < 0.001). CONCLUSION: This study revealed that there are various sociodemographic (age and year of study in BDS), academic (curricula, frequency of examination, and performance level) determinants and predictors of stress (type of accommodation), along with psychosocial stressors (parental expectation and family problems). Dental colleges should develop stress management programs to promote gender and social equity and strategies to improve psychological support services. The stress management programs reported either helped to reduce the number of stressors or enhance stress coping skills, using relaxation techniques such as deep breathing, yoga, and stress management programs.